IMF Survey, Volume 31, Issue 11. (IMF Survey; IMF Survey ;, 2002)
For many years, the IMF has tracked countries' military spending. The IMF's Fiscal Affairs Department describes its most recent findings and also looks at patterns in military as well as poverty-reducing spending in countries with loans under the IMF's concessional Poverty Reduction and Growth Facility (PRGF).